Science and innovations for food systems transformation - von Braun, Joachim; Afsana, Kaosar; Fresco, Louise O.; Hassan, Mohamed Hag Ali (Springer International Publishing :, 2023)
This Open Access book compiles the findings of the Scientific Group of the United Nations Food Systems Summit 2021 and its research partners. The Scientific Group was an independent group of 28 food systems scientists from all over the world with a mandate from the Deputy Secretary-General of the United Nations. The chapters provide science- and research-based, state-of-the-art, solution-oriented knowledge and evidence to inform the transformation of contemporary food systems in order to achieve more sustainable, equitable and resilient systems